Essay competition (2025): “Rilke today – words that remain” – an introduction - Dyballa, Jacqueline; Himmer, Johanna; Kisyova, Vian; Georgieva, Gergana; Mesova, Bianka; Babacheva, Magdalena (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2025)
To mark the 150th anniversary of Rainer Maria Rilke’s birth, this year’s essay competition organized by the Austrian Library in Sofia – in cooperation with the OeAD and the DAAD – was dedicated to the work of one of the most important German-language poets of the 20th century. School pupils and students from all over Bulgaria were invited to choose a poem by Rilke under the motto “Rilke Today – Words That Remain” and write a personal essay based on it.